Tyrosine Kinase Signaling in Cancer Metabolism: PKM2 Paradox in the Warburg Effect - Wiese, Elizabeth K.; Hitosugi, Taro (Frontiers in Cell and Developmental Biology, 2018)
The Warburg Effect, or aerobic glycolysis, is one of the major metabolic alterations observed in cancer. Hypothesized to increase a cell’s proliferative capacity via regenerating NAD+, increasing the pool of glycolytic biosynthetic intermediates, and increasing lactate production that affects the tumor microenvironment, the Warburg Effect is important for the growth and proliferation of tumor cells. The mechanisms by which a cell acquires the Warburg Effect phenotype are regulated by the expression of numerous oncogenes, including oncogenic tyrosine kinases. Oncogenic tyrosine kinases play a significant role in phosphorylating and regulating the activity of numerous metabolic enzymes. Tyrosine phosphorylation of glycolytic enzymes increases the activities of a majority of glycolytic enzymes, thus promoting increased glycolytic rate and tumor cell proliferation. Paradoxically however, tyrosine phosphorylation of pyruvate kinase M2 isoform (PKM2) results in decreased PKM2 activity and this decrease in PKM2 activity promotes the Warburg effect. Furthermore, recent studies have shown that PKM2 is also able to act as a protein kinase using phosphoenolpyruvate (PEP) as a substrate to promote tumorigenesis. Therefore, numerous recent studies have investigated both the role of the classical and non-canonical activity of PKM2 in promoting the Warburg Effect and tumor growth, which raise further interesting questions. In this review, we will summarize these recent advances revealing the importance of tyrosine kinases in the regulation of the Warburg Effect as well as the role of PKM2 in the promotion of tumor growth.